Incidence and Predictors of Subsequent Surgery following ACL Reconstruction: A 6-Year Cohort Follow-up Study. Issue 7 (31st July 2020) - Huston, Laura; Zajichek, Alex; Spindler, Kurt; ,; Sullivan, Jaron
Objectives: Subsequent surgeries after ACL reconstruction are known to negatively affect patient satisfaction and outcomes. Previous studies have identified risk factors for subsequent operations after ACL reconstruction, but few studies have identified factors which increase the risk for subsequent specific procedures related to meniscus and articular cartilage.The purpose of this study was two-fold: 1) to report the incidence and types of subsequent surgeries which occur in a cohort of ACL reconstructed patients 6 years following their index ACL reconstruction; and, 2) to predict which variables (i.e. patient demographic and surgical) may influence the incidence of a patient having a subsequent meniscus or articular cartilage related surgery following their index ACL reconstruction. Methods: This was a multicenter longitudinal prospective cohort study design. Each participant completed a questionnaire that included baseline demographics, injury descriptors, sports participation level, comorbidities, knee surgical history, and validated patient-reported outcome measures, and were followed up at 2 and 6 years. In addition, patients were also contacted to determine whether any underwent additional surgical knee procedures since baseline. Operative reports were obtained and independently read by two orthopaedic surgeons, and all procedures were categorized and recorded, along with the surgical date. If multiple procedures were done during an operation, all were recorded. Two separate logistical regression models were constructed to predict which independent variables (i.e. patient demographic and surgical) potentially influenced the incidence of a patient having a subsequent surgery following their index ACL reconstruction: model #1 examined subsequent meniscus-related surgeries on the ipsilateral knee and model #2 examined subsequent articular cartilage-related surgeries. Results: The cohort consisted of 3, 276 subjects (56% male) with a median age of 23 years at the time of enrollment. Primary ACL reconstructions comprised 93% of the group, while 7% were enrolled as revision ACL reconstructions. The majority of subjects underwent bone-patellar tendon-bone (BTB) autograft reconstructions (43%), while 34% underwent hamstring autograft and 23% had allograft reconstructions. We obtained 92% (2999/3276) follow-up with regards to information on incidence and frequency of subsequent surgeries on the cohort. The remaining 8% (277/3276) were lost to follow-up. Overall, 20% (612/2999) of the cohort was documented to have had at least one subsequent surgery on the ipsilateral knee 6 years following their index ACL reconstruction. These 612 subjects encompassed 1, 272 categorical procedures. The most common subsequent procedures on the ipsilateral knee were meniscus-related (n=357 procedures;11.9% of follow-up cohort), revision ACL reconstruction (226 procedures; 7.5% of cohort), arthrofibrosis-related (235 procedures; 7.8% of cohort), or articular cartilage-related (201 procedures; 6.7% of cohort). Collectively, subsequent procedures involving the medial meniscus (repairs and/or meniscectomies) occurred almost twice as frequently as the lateral meniscus (7.4% vs. 4.2%). Surprisingly, only 19 total knee arthroplasties (0.6% of cohort) were performed during this follow-up time period, at a median time of 45 months following the patient's index ACL reconstruction. The variables that were found to be significant predictors of having a subsequent meniscal surgery on the ipsilateral knee were patients with lower age, higher baseline Marx activity level, patients who had quit smoking (compared to non-smokers), having a autograft hamstring or allograft (compared to an autograft BTB), or having a medial meniscus repair or a medial meniscus tear that was not treated at the time of index surgery. After adjusting for all other covariates, patients with an index medial meniscus repair were 4.4 times more likely to undergo a subsequent surgery related to the meniscus than patients with no initial medial meniscal pathology. The variables that were found to be significant predictors of having a subsequent surgery involving the articular cartilage (AC) were patients with higher BMI, higher baseline Marx activity level, having an autograft hamstring or allograft (compared to an autograft BTB), having a meniscus repair at the time of index surgery, or having Grade 3 or 4 AC pathology in any compartment. Specifically, if a patient has grade 4 changes in any compartment at the time of their index reconstruction, they are over 3 times more likely to have a subsequent AC-related surgery by 6 years, after controlling for all covariates (p<0.001). Conclusion: This study identified the incidence of subsequent surgeries and risk factors for having subsequent meniscus or articular cartilage related procedures over a 6-year follow up period. Identifying and understanding these risk factors is a critical step in helping to mitigate the risks to improve patient outcomes.